Prognosis of Mechanical Ventilation in Very Low Birth Weight Neonates: A Single-Center Study in Tehran. - Karbasian, Fereshteh; Jafarian, Sara; Zafari, Ali; Bineshfar, Niloufar; Afjehi, Seyed Abolfazl; Hosseini, Amirhossein; Fallahi, Minoo (Student Research in Translational Medicine, 2020)
Background and Aims: Approximately 4–7 percent of all live births are led to a very low birth weight (VLBW) situation where the morbidity and mortality rate are very high. A large number of VLBW newborns in intensive care unit (ICU) require mechanical ventilation due to various conditions. To reduce mortality in this group, identification of risk factors is important. This study aimed to determine the prognosis of mechanical ventilation in VLBW neonates at Mahdiye hospital in Tehran. Materials and Methods: This study is a prospective cohort study. VLBW neonates who consecutively were put on mechanical ventilation during the study period were enrolled. Then, the enrolled neonates were divided into two groups: neonates who died after implementing the ventilator were in group-I and neonates who survived after receiving mechanical ventilation were in group-II. Demographic, clinical and paraclinical variables were gathered to find out the predictors of mortality of ventilated neonates. The data were analyzed by SPSS software version 21. Results: During the study period, a total of 177 neonates were ventilated due to different causes. 56% were male with a male to female ratio 1.27:1. Mean birth weight and gestational age were 1024.8 ± 247.5 grams and 27.9±2.2 weeks respectively. Out of 177 mechanically ventilated VLBW neonates enrolled for this study, 53% died. Significant factors determining mortality rate were mean weight, mean gestational age, pulmonary hemorrhage, advance resuscitation and duration of hospital stay (p<0.05). APGAR score, gender, Pneumothorax, IVH>II, Sepsis and Maternal Disease were not significantly associated with mortality in VLBW neonates requiring mechanical ventilation (P>0.05). Conclusion: This study showed that among the analyzed factors weight <1000gm, gestation <28weeks, pulmonary hemorrhage and complications during ventilation were the most significant predictors of mortality in ventilated VLBW neonates in the intensive care unit.